Certification System in Template Climate (ARQUISUR Revista, 2017)
The aim of this paper is to present the regulatory field and existing tools to certify the energy efficiency of buildings in Spain, within countries in temperate climate. Moreover, it states the documents recognized for their realization. Besides, the paper establishes their link with the European directives designed to fulfill the commitments set by The United Nations Framework Convention on Climate Change. The comparison between the different tools and with other countries will identify their strengths and weaknesses, in order to draw conclusions about the improvements that could arise from the certification process and energy efficiency to the regulations governing them.
Keywords: energetic resources; thermal energy; environment; air conditionin